Effect of Letrozole Based Intravaginal Device on Follicular Dynamics, Luteal Function and Fertility in Crossbred Cows Exhibiting Prolonged Oestrus - Aravind Suresh, Muthuvallukunnel; Pappu Unnikrishnan, Melitta; Jayakumar, Choppilil; Bibin Becha, Bahuleyan; Devassy Benjamin, Elavathinkal; Mohanan Syam Mohan, Kolamveettil (The Indian Journal of Animal Reproduction, 2025)
Eighteen cows exhibiting prolonged oestrus were randomly allotted to three groups (n=6 cows/group; Group I, II, III)  and six cows with normal duration of oestrus formed Group IV. Letrozole impregnated (37.5mg) polyurethane sponge  was used as intra-vaginal letrozole releasing device (IVLRD) and was inserted in Group I and II cows, whereas plain  intra-vaginal device (IVD-P) was inserted in Group III and IV, on day 12 of observed oestrus. The IVD was removed on  day 17 in all the groups; in Group II, 500 µg of cloprostenol was given parenterally, at the time of device removal. All the  cows were artificially inseminated (AI) in the succeeding oestrus. Blood samples were collected for serum hormone assay  and trans-rectal ultrasonography (TRUS) for ovarian dynamics were carried out in both the cycles. Pregnancy diagnosis  by TRUS was carried out on day 45 of AI. Study revealed that letrozole, along with cloprostenol significantly reduced  (p
Keywords: Prolonged oestrus; Crossbred cattle; Letrozole; Intra-vaginal device; Follicular dynamics; Luteal function